IoT system with frequency converters of physical quantities on FPGA - Osadchuk, Oleksandr V.; Osadchuk, Iaroslav O.; Skoshchuk, Valentyn K. (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The paper presents an IoT system that ensures efficient collection, processing, and transmission of measurements from multichannel radio engineering systems based on FPGA. The developed system is designed for use in remote and hard-to-reach locations, where precision, reliability, and energy efficiency are critical. The implementation integrates the LilyGo LoRa32 module, which supports modern wireless communication protocols such as LoRa, WiFi, and Bluetooth. The core of data transmission is the compact CBOR format, which minimizes the volume of transmitted data and delays. The system includes a LoRa hub capable of receiving data from numerous collection devices, consolidating them into a centralized point, and transmitting them to a server via a WiFi connection. On the server side, a REST API has been developed based on the FastAPI framework, allowing the receipt of data in CBOR format, processing it, and storing it in an SQLite database. The use of the HTTPS protocol ensures the security of transmitted data, including confidentiality, authenticity, and integrity. The server also provides clients with access to data through multiple API interfaces, facilitating easy integration with other systems. A mobile application was separately developed using Kotlin and Android Studio, providing convenient access to the collected measurements. The application supports real-time dynamic data updates, allowing users to monitor connection status, select hubs and collection devices, as well as analyze and visualize the received results. The developed IoT system demonstrates high performance and versatility, making it suitable for a wide range of applications, including industrial automation, environmental monitoring, agriculture, and other IoT scenarios. Further development of this system includes improving data processing algorithms, increasing the hub’s throughput capacity, and expanding functionality for real-time monitoring. This paves the way for the creation of innovative IoT solutions capable of meeting the demands of modern technologies in various fields.